Technique of the biomechanical analysis of execution of upward jump piked - Nataliya Batieieva; Petro Kyzim (Kharkiv State Academy of Physical Culture, 2016)
Purpose: the biomechanical analysis of execution of upward jump piked. Material & Methods: the following methods of the research were used: theoretical analysis and synthesis of data of special scientific and methodical literature; photographing, video filming, biomechanical computer analysis, pedagogical observation. Students (n=8) of the chair of national choreography of the department of choreographic art of Kiev national university of culture and art took part in carrying out the biomechanical analysis of execution of upward jump piked. Results: the biomechanical analysis of execution of upward jump piked is carried out, the kinematic characteristics (way, speed, acceleration, effort) of the general center of weight (GCW) and center of weight (CW) of biolinks of body of the executor are received (feet, shins, hips, shoulder, forearm, hands). Biokinematic models (phases) are constructed. Power characteristics are defined - mechanical work and kinetic energy of links of legs and hands at execution of upward jump piked. Conclusions: it is established that the technique of execution of upward jump piked considerably influences the level of technical training of the qualified sportsmen in gymnastics (sports), in aerobic gymnastics (aerobics), diving and dancing sports.